A Multi-Informant Approach to Exploring Connections, Disruptions, and the Multidimensional Elements of Transition to Adulthood for People with Intellectual Disabilities - Francesca Ribenfors; Sue Caton; Leanne Rimmer (Scandinavian Journal of Disability Research)
Transition to adulthood is a challenging time for young people with intellectual disabilities and their families in England. Existing research often adopts a narrow focus, concentrating on a specific area of transition or participant group. In contrast, our study employs a multi-informant approach bringing together young people with intellectual disabilities, mothers, and professionals to explore what a consideration of differing perspectives can bring to understanding of transition. A thematic analysis of focus group and interview data led to 13 subthemes organised into 3 overarching themes: The Transition Minefield, Networks of Support, and Encountering Adulthood. Examining these themes reveals the multidimensional, interconnected, and turbulent nature of transition. As such, we add to disability scholarship by providing an overview of the complexity of transition, emphasising the need to account for the wider contexts people operate in, alongside the diverse and intersecting elements shaping experiences.